2017
DOI: 10.1038/s41526-016-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

Spaceflight-induced neuroplasticity in humans as measured by MRI: what do we know so far?

Abstract: Space travel poses an enormous challenge on the human body; microgravity, ionizing radiation, absence of circadian rhythm, confinement and isolation are just some of the features associated with it. Obviously, all of the latter can have an impact on human physiology and even induce detrimental changes. Some organ systems have been studied thoroughly under space conditions, however, not much is known on the functional and morphological effects of spaceflight on the human central nervous system. Previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 108 publications
2
39
0
Order By: Relevance
“…In general, simulated microgravity studies do not include factors such as launch stress, acceleration, excitement, anxiety, prolonged isolation, and environmental parameters such as light intensity, light/dark cycles, pressure, and radiation exposure. For example, spaceflights are associated with increased stress levels, while DI and HDBR are associated with boredom due to monotony and immobilization [28]. So all or any of these factors constitute limitations, which could affect the interpretation of the results of simulation studies.…”
Section: Discussionmentioning
confidence: 99%
“…In general, simulated microgravity studies do not include factors such as launch stress, acceleration, excitement, anxiety, prolonged isolation, and environmental parameters such as light intensity, light/dark cycles, pressure, and radiation exposure. For example, spaceflights are associated with increased stress levels, while DI and HDBR are associated with boredom due to monotony and immobilization [28]. So all or any of these factors constitute limitations, which could affect the interpretation of the results of simulation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Psychology, mental heath, team performance and group interactions in space are reviewed in (Suedfeld and Steel, 2000 ; Manzey, 2004 ; Kanas and Manzey, 2008 ; Kanas, 2015 ; Salas et al, 2015 ; Pagel and Choukèr, 2016 ; Sandal, 2018 ). For a discussion of current knowledge on neuroplastic changes in the human central nervous system associated with spaceflight (actual or simulated) as measured by magnetic resonance imaging-based techniques (see Van Ombergen et al, 2017 ). Cognitive functions, human error, and workload and fatigue are relevant to expedition cognition and are amenable to study in the cave environment as discussed here; useful references for further reading include (De La Torre et al, 2012 ; Gore, 2018 ; Kanki, 2018a ).…”
Section: Scope and Terminologymentioning
confidence: 99%
“…In 2017, a review on these MRI changes associated with spaceflight (actual or simulated) was reported. Van Ombergen et al [32] discussed neuroplastic changes in the central nervous system and concluded that the cerebellum, cortical motor areas, and vestibular-related pathways are highly involved, demonstrating that these brain regions are indeed affected by actual and simulated spaceflight. Structural studies are now in progress, and functional relationships are under investigation.…”
Section: Brain Structural Plasticity During Spaceflightmentioning
confidence: 99%